β-lactoglobulin micro- and nanostructures as bioactive compounds vehicle: In vitro studies - Simões, Lívia S. (2020)
β-Lactoglobulin (β-Lg) is known to be capable to bind hydrophilic and hydrophobic bioactive compounds. This research aimed to assess the in vitro performance of β-Lg micro- (diameter ranging from 200 to 300 nm) and nano (diameter < 100 nm) structures associated to hydrophilic and hydrophobic model compounds on Caco-2 cells and under simulated gastrointestinal (GI) conditions. Riboflavin and quercetin were studied as hydrophilic and hydrophobic model compounds, respectively. Cytotoxicity experiment was conducted using in vitro cellular model based on human colon carcinoma Caco-2 cells. Moreover, the digestion process was simulated using the harmonized INFOGEST in vitro digestion model, where samples were taken at each phase of digestion process - oral, gastric and intestinal - and characterized in terms of particle size, polydispersity index (PDI), surface charge by dynamic light scattering (DLS); protein hydrolysis degree by 2,4,6-trinitrobenzene sulfonic acid (TNBSA) assay and native polyacrylamide gel electrophoresis; and bioactive compound concentration. Caco-2 cell viability was not affected up to 21 × 10−3 mg mL−1 of riboflavin and 16 × 10−3 mg mL−1 quercetin on β-Lg micro- and nanostructures. In the oral phase, β-Lg structures’ particle size, PDI and surface charge values were not changed comparing to the initial β-Lg structures (i.e., before being subjected to in vitro GI digestion). During gastric digestion, β-Lg structures were resistant to proteolytic enzymes and to acid environment of the stomach – confirmed by TNBSA and native gel electrophoresis. In vitro digestion results indicated that β-Lg micro- and nanostructures protected both hydrophilic and hydrophobic compounds from gastric conditions and deliver them to target site (i.e., intestinal phase). In addition, β-Lg structures were capable to enhance riboflavin and quercetin bioaccessibility and bioavailability potential compared to bioactive compounds in their free form. This study indicated that β-Lg micro- and nanostructures were capable to enhance hydrophilic and hydrophobic compounds bioavailability potential and they can be used as oral delivery systems.